News Approaches (Insights) to NPD on the Fashion Segment: The Power of Social Networks and the System See Now Buy Now - Takamitsu, Helen Tatiana [UNESP]; Gobbo Junior, Jose Alcides [UNESP]; Rinaldi, R.; Bandinelli, R. (Springer, 2019)
Digitization and social media have influenced retail advertising and created new forms of commerce, consumers are now accessing Facebook, Instagram, Snapchat and Twitter as well as various applications to make immediate product buying decisions. In this market scenario where consumer interaction and immediacy became important items to be considered by fashion brands, the See Now Buy Now (SNBN) business model emerges as a response to this new market. This change where the product is available for sale right after the runway show and collections launches causes changes in supply chain planning and the whole process of new product development, requiring a more flexible and adapted NPD (new product development) with new processes and timelines. Thus, this article aims to propose a holistic and hypothetical NPD model based on the Agile Stage-Gate theory, within the SEE NOW BUY NOW (SNBN) theme, with the lead user interaction as the leading process development metric.
Keywords: Fashion; Network; New product development; Fashion manufacturing industry; Supply chain; Social influences; Social media